Depth profiling of the refractive index from probe beam deflections induced by a serrated pump illumination on GaAs. Issue 5 (9th March 2017) - Liang, Lingliang; Tian, Jinshou; Wang, Tao; Wu, Shengli; Li, Fuli; Gao, Guilong
Abstract: We demonstrate a method to experimentally quantify the distribution with depth of photo-induced refractive index generated by a pump illumination, which is spatially modulated by a serrated mask on the surface of bulk GaAs. This photo-induced refractive index change distributes inhomogeneously with depth thus deflecting the probe beam transversely passing through the depth direction. The refractive index distribution with depth is deduced from the set of deflections of probe beam with respect to the propagating distances, which is collected experimentally in a pump probe arrangement. The obtained set of deflections of probe beam is theoretically proved to be reliable.